Bacterial Wilt of Southern Highbush Blueberry Caused by Ralstonia solanacearum - Philip F. Harmon; Carrie Harmon; Dave Norman (EDIS)
Bacterial wilt is a newly discovered disease of blueberry in Florida. Plants with bacterial wilt will show signs of water stress such as wilting and marginal leaf burn. The disease was initially confirmed on three farms in Florida. This 3-page fact sheet describes the symptoms, occurrence, and management of bacterial wilt in blueberry. Written by Philip F. Harmon, Carrie Harmon, and Dave Norman, and published by the Plant Pathology Department, November 2016.